(untitled) (Tanzania Medical Journal, 2021)
Tanzania Medical Journal is proud to be collaborating with the Organizing committee of the 2nd National Non-Communicable Diseases Scientific Conference in publishing the proceedings for the conference that was held on 9th - 10th November 2020, at the Julius Nyerere International Convention Center, Dar es Salaam Tanzania. The conference had a theme: “Strengthening Health Systems to Prevent and Control Non-Communicable Diseases in Tanzania”. The proceedings are presented along with the abstracts that are listed in clusters as they were presented during the conference, and whenever appropriated first authors affiliation is also listed. The scientific committee for this conference was responsible for peer review of the abstracts.